Nano-Biochar Prepared from High-Pressure Homogenization Improves Thermal Conductivity of Ethylene Glycol-Based Coolant - Youheng Wang; Xianjun Hou; Hong Yu; Weiwei Guan; Yuxin Ma; Mohamed Kamal Ahmed Ali (Nanomaterials, 2024)
As an environmentally friendly material, biochar is increasingly being utilized in the field of heat transfer and thermal conduction. In this study, nano-biochar was prepared from high-pressure homogenization (HPH) using sesame stalks as the raw material. It was incorporated into ethylene glycol (EG) and its dispersion stability, viscosity, and thermal conductivity were investigated. The nano-biochar was stably dispersed in EG for 28 days. When the concentration of the nano-biochar added to EG was less than 1%, the impact on viscosity was negligible. The addition of 5 wt.% nano-biochar to EG improved the thermal conductivity by 6.72%, which could be attributed to the graphitized structure and Brownian motion of the nano-biochar. Overall, nano-biochar has the potential to be applied in automotive thermal management.